The Examination of the Effect of Participation in Entrepreneurial Development Programmes on Enterprise Performance: A Case of Small-Scale Business in Nigeria - Olugbenga, Aribaba Foluso (Mediterranean Journal of Social Sciences, 2013)
Entrepreneurial Development programmes have contributed significantly to small-scale business development. Their impactincludes increased business income, accelerated business growth, improved productivity and increased sales. The successstory of Entrepreneurial Development programmes notwithstanding, they have problem of excluding small entrepreneurs dueto accessibility of the programmes, finance, timing duration and lack of awareness of the programme. This study examined theeffect of Entrepreneurial Development programmes on enterprises development and performance.The study area was OndoState of Nigeria. The study carried out a comparative study of different types of small-scale business entrepreneurs.Questionnaires were administered to small-scale business entrepreneurs. This study concluded that participation inEntrepreneurial Development programmes had a positive impact on the performance of small-scale business in Nigeria.